Increased biomass production of lettuce (Lactuca sativa L.) through nutrient management in a red hybrid tilapia (Oreochromis spp.) based on decoupled recirculation aquaponics system - Altawaha, Abdel Razzaq Mohammad (2021)
Improved aquaponics systems (APS) by adopting the decoupled recirculating aquaponics system (DRAPS) that has two independent circulations where can be controlled the physical and chemical characteristics of the water for the fish and plant independently and ability to supply macronutrients and micronutrients at an optimum concentration for plants is one of the most effective solutions to address food security issues. Thus, this study was conducted, and it consisted of four experiments. The first experiment was conducted based on a randomized complete block design (RCBD) to determine the ideal stocking density among 8 kg m-3 , 10 kg m-3 , and 12 kg m-3 and its effects on water quality, weight gain of tilapia and butterhead lettuce in the DRAPS. The results of the first experiment showed that the highest stocking density produced the highest concentrations of ammonia-nitrogen (NH3-N), ammonium (NH4), nitrate-nitrogen (NO3-N), and potassium (K). It was reported that DRAPS that relied solely on fish waste would have an insufficient concentration of nitrogen (N), phosphorus (P), K, and iron (Fe). However, the results also showed that while the lowest stocking density (8 kg m-3 ) produced the highest yield of butterhead lettuce, they were lower than the marketable yield of 150 g plant-1 . The lowest stocking density of 8 kg m-3 was subsequently used in the second experiment to evaluate the effects of three ratios of nitrate to urea±nickel (Ni) at (60:40–Ni, 60:40+Ni, and 100:0 as control) and two different seedling ages (14 days and 21 days) on the growth, yield, and the leaf nutrient content of the butterhead lettuce in DRAPS. The experimental design was based on an RCBD split-plot design with nitrate: urea ratio as the main plot, seedling age as the sub-plot, and three replicates for each treatment. The results showed that the shoot fresh weight of the butterhead lettuce transplanted at the seedling age of 21 days and supplemented with nitrate urea ratios of 60:40–Ni and 60:40+Ni decreased by 40.8% and 43.5%, respectively as compared to that supplemented with nitrate urea at the ratio of 100:0. When the lettuce was supplemented with fertilizer at the ratio of 100:0, the total shoot weight of the lettuce transplanted at the seedling age of 14 days decreased by 20.8% as compared to that of the 21-day. It was observed that the lettuce that was supplemented with Ni produced higher leaf N, K, sodium (Na), and Fe contents than those without Ni. Controlling the pH and introducing inorganic fertilizer in the second loop of DRAPS had significantly increased the total fresh yield per unit area by 91% compared to that as reported in Chapter 3. The nitrate urea ratio of 100:0 and seedling age of 21 days were determined as the ideal treatments and they were used in the third experiment. It was observed from experiments 1 and 2 that Fe is one of the most limited micronutrients in APS. Therefore, the third experiment was conducted to evaluate the effects of Fe sources and nutrient solution on the growth, yield, and leaf nutrient content of the salad in DRAPS. The experiment was set up as a factorial with two factors (first factor: Fe-sources [Fe-DTPA and Fe-EDTA]; second factor: Nutrient solution [inorganic fertilizer and recycled nutrient solution]) based on an RCBD with three replicates for each treatment. The results showed that the highest total fresh weight of the salad was detected in the DRAPS treated with Fe-DTPA and complemented nutrient solution which was 6.2% higher than those in the DRAPS treated with Fe-EDTA from the same season. The optimum planting density (PD) should be determined according to agronomic assessment, which takes growth performance, water use efficiency (WUE), and recycled nutrient solution use efficiency into consideration. In this context, the effects of two PD (16 plants m-2 and 32 plants m-2 ) and two nutrient solutions on the salad in DRAPS were studied in the fourth experiment. The ideal stocking density (Experiment 1), nitrate urea ratio, seedling age (Experiment 2), and Fe source (Experiment 3) were used in this experiment. The highest shoot fresh weight of the butterhead lettuce was recorded in the interaction of PD of 16 plant m-2 and complemented nutrient solution, while the highest total fresh weight was recorded in the PD of 32 plants m-2 and Complemented nutrient solution. The results collected from all four experiments demonstrated the potential of DRAPS in optimizing nutrient availability and increasing the butterhead lettuce biomass production. In conclusion, this study had successfully used DRAPS to produce butterhead lettuce and tilapia, which has proven the sustainability of DRAPS with two independent loops as an agricultural production system capable of increasing WUE and minimizing the inorganic nutrient supplements by integrating the production of fish and plant.